Hypothermic machine perfusion improves Doppler ultrasonography resistive indices and long‐term allograft function after renal transplantation: a single‐centre analysis. (24th May 2015) - Dion, Marie S.; McGregor, Thomas B.; McAlister, Vivian C.; Luke, Patrick P.; Sener, Alp
Abstract : Objectives: To evaluate whether hypothermic machine perfusion (HMP) of transplanted kidneys can improve long‐term renal allograft function compared with static cold storage (CS). Methods: We evaluated whether graft Doppler ultrasonography resistive indices improved with the use of HMP compared with CS preservation, and examined whether these improvements were predictive of long‐term graft function. A total of 30 kidney transplants (15 pairs) were examined. One of the kidney pairs was placed on CS and transplanted first (CS group, n = 15). The other kidney of each pair was placed on HMP and transplanted after the CS group (HMP group, n = 15). Doppler ultrasonography was performed on days 1 and 7 after transplantation and resistive indices were evaluated. The estimated glomerular filtration rate (eGFR) was monitored for 24 months after transplantation. Results: Despite longer cold ischaemia times, kidneys maintained with HMP had lower resistive indices ( P = 0.005) with correspondingly higher eGFR throughout the follow‐up. Subgroup analysis showed that the HMP‐induced improvement in postoperative eGFR was greatest in kidneys obtained from donation after cardiac death (DCD), even at 2 years after transplantation ( P = 0.008). Conclusions: HMP of transplant kidneys appears to improve vascular resistance after transplantation and has a positive impact on long‐term allograft function compared with CS in the population of recipients of DCD kidneys.